Backtracking search algorithm for optimal power dispatch in power system / Mostafa Modiri Delshad - Mostafa, Modiri Delshad (2016)

(untitled)
The solution to power dispatch problem has been an important and basic optimization procedure in both conventional and restructured power systems. The main objectives of the power dispatch problem are to minimize the generation cost and emission amount of generators as well as to meet the power demand. The goal is to determine the most optimal power sharing among the generating units in a power system. The practical power dispatch problems consider the technical operating constraints of generators such as ramp-up and ramp-down limits, lower and upper limits of generators, and prohibited operating zones. The accurate cost function needs to be taken into account in the problems for real-world applications by considering the valve-point loading effects and multiple fuel options. In this thesis, the power dispatch problems with the aforementioned constraints and cost functions are considered. Several case studies varied in size and complexity are employed in the power dispatch problems. Backtracking search algorithm (BSA) as the new evolutionary technique of optimization is used for solving the problems. Since the power dispatch problem is a constrained problem, two constraint handling mechanisms are proposed in the optimizer and are compared to each other in terms of solution quality they produce. BSA with two constraint handling mechanisms is applied to solve the power dispatch problems to select the better mechanism in power dispatch problems. Then, a microgrid with several renewable and conventional generating units is modeled for the purpose of optimal power dispatch. The problem is solved by BSA with the selected constraint handling mechanism to minimize the generation cost of the microgrid for a specific period of time. The multi-objective BSA is also developed to solve the economic and emission dispatch problems (EED) in a power system. The EED problem is solved by three methodologies including economic and emission dispatch separately, combined iv economic and emission dispatch, and economic and emission dispatches simultaneously. The high performance of the proposed technique with the proposed constraint handling mechanism is validated by solving the power dispatch problem in the large-scale test systems with the most complex cost functions. The proposed method is also compared with other well-known optimization methods from the literature in terms of the solution quality. The results show that the proposed method is highly robust when it deals with the practical power dispatch problems and its convergence characteristics make it a promising solution approach for power dispatch problems.